2014
DOI: 10.1037/a0033670
|View full text |Cite
|
Sign up to set email alerts
|

Semantic preview benefit during reading.

Abstract: Word features in parafoveal vision influence eye movements during reading. The question of whether readers extract semantic information from parafoveal words was studied in 3 experiments by using a gaze-contingent display change technique. Subjects read German sentences containing 1 of several preview words that were replaced by a target word during the saccade to the preview (boundary paradigm). In the 1st experiment the preview word was semantically related or unrelated to the target. Fixation durations on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 119 publications
(234 reference statements)
9
156
4
1
Order By: Relevance
“…Similarly, in other trials of the experiment, which manipulated preview with the boundary paradigm, a semantically related preview word did not lead to shorter FDs or different brain responses than an unrelated preview word. These results stand in contrast to demonstrations of semantic relatedness with the boundary paradigm during reading of sentences (i.e., four experiments in Hohenstein and Kliegl 2012; see also Hohenstein et al 2010, for evidence with a different, that is, parafoveal fast priming paradigm). Obviously, there are many empirical issues that remain to be sorted out, but we close with the observation that our research program on coregistration of EMs and brain potentials during reading closely recapitulated the development of eye-movement research on reading in a timecompressed manner.…”
Section: Outlook: Gaze-contingent Display Change Experimentscontrasting
confidence: 99%
“…Similarly, in other trials of the experiment, which manipulated preview with the boundary paradigm, a semantically related preview word did not lead to shorter FDs or different brain responses than an unrelated preview word. These results stand in contrast to demonstrations of semantic relatedness with the boundary paradigm during reading of sentences (i.e., four experiments in Hohenstein and Kliegl 2012; see also Hohenstein et al 2010, for evidence with a different, that is, parafoveal fast priming paradigm). Obviously, there are many empirical issues that remain to be sorted out, but we close with the observation that our research program on coregistration of EMs and brain potentials during reading closely recapitulated the development of eye-movement research on reading in a timecompressed manner.…”
Section: Outlook: Gaze-contingent Display Change Experimentscontrasting
confidence: 99%
“…There is considerable additional evidence for parafoveal (morpho-)semantic processing in Chinese (Yan, Pan, Bélanger, & Shu, 2015;Yan & Sommer, 2015;Yen, Tsai, Tzeng, & Hung, 2008). In contrast, such effects appear to be limited to synonym previews in English (Schotter, 2013) or to scripts with relatively transparent letter-phoneme correspondence, such as German (Hohenstein, Laubrock, & Kliegl, 2010;Hohenstein & Kliegl, 2014). Because alphabetic writing systems vary in their orthographic depth (i.e., the degree to which they are regular in their representation of sound), Hohenstein et al (2010) argued that, as compared to English, a more transparent orthography-to-phonology mapping in German leads to faster phonological decoding, which in turn facilitates access to semantics during the short fixation periods.…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing the gaze-contingent boundary paradigm (Rayner, 1975) have shown that reading is facilitated when a valid preview of the upcoming word is available in the parafovea. Although it is well established that this preview benefit also extends to items that share orthographic and/or phonological features with the target word (see Schotter, Angele, & Rayner, 2012), more recent studies have suggested that parafoveal words are sometimes processed to the semantic level (Hohenstein & Kliegl, 2014;Schotter, 2013;Schotter, Lee, Reiderman, & Rayner, 2015;Veldre & Andrews, 2016b). This evidence has raised questions about the precise mechanisms underlying preview effects.…”
Section: Text Comprehensionmentioning
confidence: 99%